Repeated intravesical injections of platelet-rich plasma are safe and effective in the treatment of interstitial cystitis/bladder pain syndrome - Wan-Ru Yu; Yuan-Hong Jiang; Jia-Fong Jhang; Hann-Chorng Kuo (Tzu Chi Medical Journal)
Objectives: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a challenging chronic inflammatory condition affecting the urinary bladder, with limited treatment options. This study aims to assess the clinical efficacy of repeated intravesical platelet-rich plasma (PRP) injections for promoting urothelial regeneration and reducing inflammation in patients with IC/BPS and investigate its correlation with subjective and objective treatment-related outcomes. Materials and Methods: Four monthly intravesical PRP injections were given to 98 patients with non-Hunner-type IC/BPS. Treatment outcomes were assessed using a global response assessment (GRA) score 3 months posttreatment. In addition, clinical symptom scores, pain severity, voiding diary data, uroflowmetry parameters, and GRA scores were compared before and after treatment and between different treatment outcome groups (satisfactory: GRA≥2 unsatisfactory: GRA<2). Baseline urine biomarkers were analyzed to identify potential treatment outcome predictors. Results: After four PRP injections, 54 (55.1%) patients reported satisfactory outcomes. Lower urinary tract symptoms, bladder pain, urinary frequency, anxiety, and flow rate significantly improved from baseline (P < 0.05) in all patients, regardless of the treatment outcome. All patients experienced improved treatment outcomes and increased maximum bladder capacity with successive PRP treatments, and no major complications were reported. Urine biomarkers indicated elevated inflammation and oxidative stress biomarkers in patients with IC/BPS compared to controls. Conclusion: Repeated PRP injections are safe and effective for reducing symptoms and bladder pain and improving bladder capacity in a majority of IC/BPS patients, with better outcomes observed in patients with a mild form of bladder inflammation. These results support PRP as a promising novel bladder therapy for IC/BPS.